THE EFFECT OF USING CIRC IN TEACHING WRITING NARRATIVE TEXT AT GRADE XI STUDENTS OF SENIOR HIGH SCHOOL - Juni Anto Manullang; I Wayan Dirgeyasa; Yeni Erlita (GENRE JOURNAL : Journal of Applied Linguistics of FBS Unimed, 2017)
The objective of this study was to find out whether the effect of using CIRC technique in writing narrative can improve students’ achievement in writing narrative text. It was conducted by using experimental research. The population of this study was eleventh grade of SMAN 1 Siempat Nempu Hulu, which was consisted of 4 classes. Two classes were taken as the sample by using random sampling technique. The class XI IPA 1 was as experimental group and XI IPA 2 was as the control group. The experimental group was taught by using CIRC, otherwise control group was taught by using conventional technique. The instrument for collecting data was writing test. The data were analyzed by using t-test formula. The result shows that CIRC has a significant effect on students achievement in writing narrative text. The result shows that the t-observed is higher than t-table (3.102 > 2.024 (α=0.05)) with the degree of freedom (df) = 20. Therefore, CIRC significantly affects on the students’ ability in writing narrative text. Keyword: Cooperative Integrated Reading and Composition (CIRC ), Writing, Narrative text.